2004
DOI: 10.1074/jbc.m300541200
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Heparanase Protein Is Regulated by Glycosylation in Human Tumor Cell Lines

Abstract: The endo-␤-D-glucuronidase, heparanase, is capable of specifically degrading heparan sulfate, and this activity is associated with the metastatic potential of tumor cells. The predicted amino acid sequence of heparanase includes six putative N-glycosylation sites; however, the precise biochemical role of glycosylated heparanase remains unknown. In this study, we examined the link between glycosylation and the function of heparanase in human tumor cell lines. Heparanase protein was glycosylated at six Asn resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 48 publications
(53 reference statements)
0
47
2
Order By: Relevance
“…Our results suggest that differences in molecular weights between Spalax and human heparanases are primarily due to a lower glycosylation of the Spalax protein, which lacks three of the six N-glycosylation sites of the human heparanase. Glycosylation of heparanase is not required for its enzymatic activity but may function in heparanase trafficking and secretion (43). Secretion of heparanase appears to be a cardinal step in its processing and activation (34 between the proton donor (Glu-256) and nucleophile (Glu-374) sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that differences in molecular weights between Spalax and human heparanases are primarily due to a lower glycosylation of the Spalax protein, which lacks three of the six N-glycosylation sites of the human heparanase. Glycosylation of heparanase is not required for its enzymatic activity but may function in heparanase trafficking and secretion (43). Secretion of heparanase appears to be a cardinal step in its processing and activation (34 between the proton donor (Glu-256) and nucleophile (Glu-374) sites.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 6% charged glycans were not identified, as they were not cleaved by either enzyme, presumably due to glycans inaccessible to the enzymes. The existence of six glycosylation sites in the heparanase molecule (Simizu et al, 2004), together with the homogenous appearance of the protein in a native polyacrylamide gel and the finding that 16% of the molecules carry phosphorylated high mannose led us to estimate that each heparanase molecule bears one phosphorylated glycan.…”
Section: Analysis Of Heparanase Glycan Compositionmentioning
confidence: 99%
“…Heparanase has long been characterized as a glycoprotein and including Concanavalin A affinity chromatography in the purification scheme brought this feature into practice (Toyoshima and Nakajima, 1999;Zcharia et al, 2005). Six glycosylation sites were identified in the 50 kDa heparanase subunit (Hulett et al, 1999), and their role in protein secretion was established (Simizu et al, 2004), yet glycan biochemical analysis was not performed to date.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that these six putative N-glycosylation sites were glycosylated in cultured cells. 24) Although glycosylation was not required for enzyme activity, the secretion of heparanase was regulated by glycosylation. 24) The sequence also contains a 35-amino-acid N-terminal signal sequence (Met 1 -Ala 35 ), which represents the most prominent difference between the chicken and human enzymes, and which apparently accounts for the fact that chicken heparanase is readily secreted.…”
Section: Heparanase Structurementioning
confidence: 99%
“…24) Although glycosylation was not required for enzyme activity, the secretion of heparanase was regulated by glycosylation. 24) The sequence also contains a 35-amino-acid N-terminal signal sequence (Met 1 -Ala 35 ), which represents the most prominent difference between the chicken and human enzymes, and which apparently accounts for the fact that chicken heparanase is readily secreted. 25) Use of a chimeric construct composed of the human enzyme and the chicken heparanase signal peptide revealed that cell surface localization and the secretion of heparanase markedly stimulated tumor angiogenesis.…”
Section: Heparanase Structurementioning
confidence: 99%